PEMBIASAAN SHALAT BERJAMAAH DALAM MENANAMKAN KARAKTER RELIGIUS ANAK USIA 5-6 TAHUN DI RA AL-IZZAH KOTA SERANG BANTEN: ANAK USIA 5-6 TAHUN DI RA AL-IZZAH KOTA SERANG BANTEN - Muslimah, Rosailatul; Fadlullah; Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Rosailatul Muslimah (2228210019) The Habit of Congregational Prayer in Instilling Religious Character in Children Aged 5-6 Years at RA Al-Izzah, Serang City, Banten. Undergraduate Thesis (S-1) Program, Early Childhood Education Teacher Education Department. Faculty of Teacher Training and Education. Sultan Ageng Tirtayasa University. This study explains the habit of congregational prayer in instilling religious character in children aged 5-6 years at RA Al Izzah, Serang City, Banten. The method used in this study is qualitative research and is analyzed by means of descriptive analysis that clearly explains the data collected, and then uses a case study with an in-depth approach that emphasizes a deep understanding of the habit of congregational prayer in instilling religious character in children aged 5-6 years at RA Al-Izzah, Serang City. Based on the results of the research that has been carried out, it can be concluded that the implementation of the habit of congregational prayer in instilling the religious character of children aged 5-6 years, which is integrated into an integrated curriculum, is effective in developing the religious and social character of children aged 5-6 years. Supported by adequate human resources, good facilities, and cooperation with parents, this program has succeeded in instilling religious values, discipline, and togetherness. The evaluation showed satisfactory results, with high target achievements and a positive impact on the development of children's character holistically.